Optimizing Strategy of Subsidized Fertilizer Distribution to POKTAN (Farmer Groups) - Arodha, Dianidza (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
This study examines the optimization of subsidized fertilizer distribution strategies aimed at improving accessibility, efficiency, and precision in reaching farmer groups. Subsidized fertilizer distribution plays a critical role in supporting agricultural productivity, yet inefficiencies often arise due to logistical challenges, inaccurate data management, and limited resources. Utilizing a case study approach, this research explores how a structured distribution strategy can address these issues by focusing on key areas: expanding distribution networks, implementing integrated digital data systems, enhancing logistics capacity, and aligning with government policies for subsidized programs. Data collection includes interviews with distribution managers, observational analysis of operational workflows, and document analysis of logistical records and digital tracking systems. Findings suggest that optimizing distribution requires a combination of increasing logistical resources, adopting digital tools, and fostering government collaboration to maintain affordability.